CCBC Choices 2010 - Michaelson, Tessa; Schliesman, Megan; Lindgren, Merri V.; Horning, Kathleen T. (My University, 2010)
CCBC CHOICES is an annual list of recommended books for children and young adults selected by the librarians at the Cooperative Children's Book Center, a library of the School of Education at the University of Wisconsin-Madison. CCBC CHOICES 2010 recommends 235 titles for children and young adults published in 2009. It includes a commentary on the 2009 ublishing year, including statistics on the number of books by and about people of color published for children and teens.
Keywords: children's literature, young adult literature, multicultural literature